Aristotelian Ethics and Politics: A Solution for Today - Massias, Georgios (Conatus - Journal of Philosophy, 2018)
Aristotle famously classified virtue as cognitive and moral, deriving from any human being's scientific and calculative part of the soul respectively; any person that achieves both will definitely experience eudemonia. In this paper I will advocate Aristotle's view, and I will assume that the reason why there is widespread lack of eudemonia today is that modern man has systematically been neglecting moral virtues.